Panel Data Analysis 1992
DOI: 10.1007/978-3-642-50127-2_2
|View full text |Cite
|
Sign up to set email alerts
|

Can Cohort Data be Treated as Genuine Panel Data?

Abstract: If repeated observations on the same individuals are not available it is not possible to capture unobserved individua: chara.cteristics in a linear model by using the fixPd effects estimator in the standard way. If large numbers ot observations are available in each period one can use cohorts of individuals with common characteristics to achieve the same goal, as shown by Deaton (19}i5]. It is tempting to analyze the observations on cohort averages as if they are observation~on iodividua!s~.vhich are observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
111
0
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(117 citation statements)
references
References 5 publications
2
111
0
4
Order By: Relevance
“…9 For empirical production studies using such panel data, the temporal pattern of a given farm's production behavior must be established. In the absence of genuine panel data, repeated cross-sections of data across farm typologies may be used to construct pseudo panel data (see Deaton, 1985;Heshmati and Kumbhakar, 1997;Verbeek and Nijman, 1992). Such a panel is created by grouping the individual observations into homogeneous cohorts, distinguished according to time-invariant characteristics such as fixed assets, geographic location, or land quality or acreage.…”
Section: The Us Agriculture Panel Datamentioning
confidence: 99%
“…9 For empirical production studies using such panel data, the temporal pattern of a given farm's production behavior must be established. In the absence of genuine panel data, repeated cross-sections of data across farm typologies may be used to construct pseudo panel data (see Deaton, 1985;Heshmati and Kumbhakar, 1997;Verbeek and Nijman, 1992). Such a panel is created by grouping the individual observations into homogeneous cohorts, distinguished according to time-invariant characteristics such as fixed assets, geographic location, or land quality or acreage.…”
Section: The Us Agriculture Panel Datamentioning
confidence: 99%
“…Researchers (e.g., Moffitt 1993; Verbeek and Nijman 1992) have suggested that cross-sectional data constructed as cohorts can be treated as genuine panel data, with some limitations. If these limitations can be addressed, analyses with constructed cohorts can expand our understanding of intergenerational change, such as the effects of family environments on child development, educational achievement, and employment prospects that otherwise are unavailable in low- and middle-income countries (LMICs) given the paucity of large-scale, longitudinal population data.…”
Section: Source Of Data and Measurementmentioning
confidence: 99%
“…The obtained cohort averages, however, are consistent, unbiased estimates of the true population cohort means, with the difference resulting from sampling error. Studies have shown that such measurement error is negligible, however, when the cohort size is sufficiently large (Verbeek and Nijman 1992). In this analysis, we use means based on only those cohorts with 100 or more members, as recommended by Verbeek and Nijman (1992).…”
Section: Source Of Data and Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…However, alternative sources of data, which have many of the advantages of longitudinal data, are independent cross-sectional surveys that can be used to construct a synthetic panel. Such data follow cohorts of individuals over time where cohorts are defined by time-invariant variables, in this case year of birth, gender and Indigenous origin (see Deaton 1985;Verbeek and Nijman 1992). This article uses individuallevel data to construct a synthetic panel (sometimes referred to as a pseudo panel) of Indigenous and non-Indigenous Australians using data from the 1981, 1986, 1991 and 1996 censuses, to present the first longitudinal estimates of the determinants of Indigenous and non-Indigenous employment and labour force participation.…”
Section: Introductionmentioning
confidence: 99%